PERAN KOMUNIKASI DAKWAH ABDUR RAUF AS-SINGKILI SEBAGAI MUFTI KERAJAAN ACEH - Ramadan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Sheikh Abdurrauf As-Singkili, he is a figure who played an important role in spreading Islamic teachings through the spread of Islam in the Barus (Fansur) area which is usually called Singkil. This is proven by his work which is developing rapidly in the Kingdom of Aceh and becoming a reference in the world of education. This is proven by his work which is developing rapidly in the Kingdom of Aceh. He developed Islamic da'wah/education from Fansur to the Kingdom of Aceh and even internationally. Islam is widespread in Aceh, especially in Singkil. In this research, an interesting strategy was used, specifically collecting data on Abdurrauf As-Singkili's commitment to the central issues he wanted to study. At the information gathering stage, a library exploration will be carried out, then the information examination will be completed as a satisfactory investigation. This research concludes, based on data analysis of Abdurrauf As-Singkili's contribution, there is no doubt that Abdul Ruf Singkel is a figure who plays a role and has sharp thinking, and is famous for his knowledge. His role in Aceh is demonstrated through his important scientific works, as an influential thinker and intellectual among Muslims who is very well known in Indonesia. From the writings of previous Islamic ulama thinkers to the present, there are many works such as suluk and others. The Dutch university library still has a copy of the original text or handwritten manuscript, so he was appointed mufti of the kingdom of Aceh.